Sedimentation and transformation in organizational change: The case of management training - Silva, M. G. (Proceedings of the 5th Global Management Conference on Managing Globalization in Times of Economic Crisis, 2013)
This study aims to contribute to a more complete understanding of planned change interventions on human processes by presenting a selective interdisciplinary history of management training programmes. Drawing on the simplistic notion of ‘homo economicus’, training activities often focus on institutional design and the intentional process made by interested parties towards improving effectiveness. This work develops a vision that challenges the application of universal recipes to bring change in organizations and discusses directions for future research.